Antiferromagnetic textures in BiFeO3 controlled by strain and electric field - A. Haykal (Nature Portfolio, 2020)
Tailoring antiferromagnetic domains is critical for the development of low-dissipative spintronic and magnonic devices. Here the authors demonstrate the control of antiferromagnetic spin textures in multiferroic bismuth ferrite thin films using strain and electric fields.